Changes in Eating Habits and Sedentary Behavior During the COVID-19 Pandemic in Adolescents With Chronic Conditions - Mazzolani, Bruna Caruso; Smaira, Fabiana Infante; Astley, Camilla; Iraha, Amanda Yuri; Pinto, Ana Jessica; Marques, Isabela Gouveia; Cordeiro Amarante, Milla; Rezende, Nathalia Saffioti; Sieczkowska, Sofia Mendes; Franco, Tathiane Christine; Miranda, Luana Cristina do Amaral; Lindoso, Lívia; et al. (Frontiers in Pediatrics, 2021)
Introduction: Among healthy adolescents, school closures and home confinement were shown to increase unhealthier eating habits and sedentary behavior. It remains unknown to which extent the pandemic has impacted the lifestyle of adolescents with chronic conditions. Thus, the aim of this study is to report on the impact of the COVID-19 outbreak on eating habits and sedentary behavior among adolescents with multiple chronic conditions (n=347) from a tertiary, referral hospital vs. healthy peers. Methods: This observational study was conducted in Sao Paulo (Brazil) between July and October 2020, period in which a set of social distancing measures to contain the pandemic. Results: The main findings of this study were that adolescents with chronic conditions and health peers showed important changes in eating habits (e.g., more often cooking and eating in front of television than before quarantine). Also, 86.8% of adolescents with chronic conditions and 91.6% of healthy adolescents reported increasing screen time during pandemic. No major differences were observed between patients and controls. Conclusions: Adolescents with chronic conditions and healthy peers exposed to pandemic showed substantial changes in lifestyle, stressing the need for specific care to mitigate poor eating habits and excessive sedentary behavior for patients and healthy adolescents.